Remediation of water contaminated with polycyclic aromatic hydrocarbons using liquid phase plasma: Influence of electrical discharge condition - Kim, Ui-Jun; Saito, Nagahiro; Lee, Seung-Hyo (Frontiers in Marine Science, 2022)
Although the number of vessels with exhaust gas cleaning systems (EGCSs or scrubbers) has sharply increased to comply with strengthened regulations for marine environment, secondary pollutions are caused by discharged polycyclic aromatic hydrocarbons (PAHs) from scrubber effluent. Here, liquid-phase plasma (LPP) is employed to remediate water contaminated with PAHs. The increased frequency and pulse width enhanced the degradation efficiency, and 93.3, 90.7, 86.0, and 85.4% for naphthalene (Nap), acenaphthene (Ace), fluorene (Flu), and phenanthrene (Phe), respectively, are degraded at a frequency of 30 kHz and pulse width of 3 μs in 10 min. Considering physical condition of the plasma, long pulse width accelerated electrons, leading to increased generation of active species from intensified collision between electrons and surrounding molecules. Conversely, high frequency decelerated electrons due to the excessive changes in the polarity. However, the increased number of plasma discharges results in the generation of numerous active species. Generations of •OH and O radicals are confirmed by optical emission spectrometry and electron paramagnetic resonance. In addition, changes in functional groups which are corresponding to hydroxyl and oxygen groups are identified by Fourier transform infrared spectroscopy. Total PAHs in real scrubber are reduced from 1.1 to 0.4 μgL-1 with degradation efficiency of 63.6% after 10 min of LPP treatment. This study suggests LPP can be a promising method to protect diverse aqueous environments and provides optimal electrical discharge condition for degradation of organic pollutants.